Pembelajaran Inklusif: Peran Komunikasi Multikultural dalam Menangani Keragaman Budaya di Lingkungan Sekolah - Mustain Mustain (https://journal.metanusantara.com/pedagogia, 2024)
This research aims to examine the role of multicultural communication in inclusive learning in schools with cultural diversity. The approach used is qualitative with a case study method, where data is obtained through in-depth interviews, participatory observation, and document analysis. The main informants in this study include teachers, principals, and students from several inclusive primary schools. The main objectives of this research are to understand how multicultural communication strategies are implemented in the context of inclusive learning, identify the challenges faced, and evaluate the effectiveness of the approach in creating a harmonious and inclusive learning environment. The results show that teachers in inclusive schools have implemented various communication strategies to accommodate students' cultural diversity. These strategies include the use of language that is easily understood by all students, the integration of teaching materials that reflect various cultures, and the application of participatory teaching methods that encourage intercultural interaction. In addition, teachers act as facilitators in intercultural discussions, allowing students to share their experiences and perspectives. However, this study also identified a number of challenges, such as language differences that cause difficulties in understanding the material, the existence of stereotypes and prejudices among students, as well as resource limitations such as the lack of teaching materials that reflect cultural diversity and the need for training for teachers in managing multicultural classrooms.